The Influence of Influencer Marketing and Brand Image on Skintific Skincare Product Purchasing Decisions among Generation Z in Surabaya - Riliani Melanovita Sari; Jimmy Ignatius; Ageng Pratiwi (Escalate : Economics and Business Journal, 2026)
This study aims to analyze the influence of Influencer Marketing and Brand Image on purchasing decisions for Skintific skincare products among Generation Z in Surabaya. This research used a quantitative approach with data collection methods conducted through questionnaires distributed to Generation Z respondents aged 14–29 years who had used Skintific skincare products. The sampling technique used was non-probability sampling with a purposive sampling method. The total sample in this study consisted of 100 respondents obtained using the Slovin formula. The data analysis technique used multiple linear regression analysis with the assistance of SPSS (Statistical Package for the Social Sciences). The results showed that Influencer Marketing had a positive and significant effect on purchasing decisions with a t-count value of 6.432 > t-table 1.98472 and a significant value of 0.000 < 0.05. Brand Image also has a significant effect on purchasing decisions with a t-count value of 5.324 > t-table 1.98472 and a significant value of 0.000 < 0.05. In addition, the F-test results indicated that Influencer Marketing and Brand Image simultaneously had a significant effect on purchasing decisions with an f-count value of 60.165 > f-table 3.09 and a significant value of 0.000 < 0.05. Therefore, Influencer Marketing and Brand Image play an important role in increasing purchasing decisions for Skintific skincare products among Generation Z in Surabaya.